Deleterious Effects of Methylene Blue on Rat Nucleus Pulposus Cell in Vitro: Changes in Cell Viability and Secretory Phenotype in Exposed Cells - Wang, Xiaohu; Zhang, Shaodong; Xie, Zhiyang; Chen, Lu; Yang, Baolin; Wu, Xiaotao (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Purpose To investigate the effects of methylene blue (MB) on the viability and secretory phenotype of rat nucleus pulposus (NP) cells in vitro.Methods Rat NP cells were isolated, cultured, and treated with different MB concentrations (0–6.25 ng/mL) for different lengths of time. We evaluated the changes in cell morphology and cell viability. We also examined the cells for expression of collagen II, aggrecan, matrix metalloproteinase (MMP)-3, MMP-9, and inducible nitric oxide synthase (iNOS).Results After 2.5 to 6.25 ng/mL MB induced for 6 hours, numerous NP cells were dyed blue and rounded up. The adherent cell number was reduced by MB treatment. The viability of rat NP cells was significantly inhibited by MB in a dose- and time-dependent manner. Treatment with a very low dose of MB (1.5625 ng/mL) resulted in lower expression of collagen II and aggrecan and higher expression of MMP-3, MMP-9, and iNOS in rat NP cells.Conclusions Rat NP cells exposed in vitro to MB significantly reduced their viability. Moreover, MB upregulated catabolism gene expression and downregulated anabolism gene expression in rat NP cells. These results suggest MB may be harmful to NP cells. The dose of intradiskal injected MB should be as low as possible to prevent or limit the damage to intervertebral disks.
Keywords: methylene blue; cell viability; nucleus pulposus cell; percutaneous endoscopic lumbar diskectomy; intervertebral disk degeneration